2015 IEEE 15th International Conference on Advanced Learning Technologies 2015
DOI: 10.1109/icalt.2015.122
|View full text |Cite
|
Sign up to set email alerts
|

Online Peer Learning: What Influences the Students' Learning Experience

Abstract: This paper reports on the preliminary findings of a research-in-progress project investigating what factors influence the students' learning experience while they study in an online environment. Online peer learning activities combined with current technology are expected to improve students' learning experience. The students were asked to respond to an online survey and attend virtual focus groups. Semi-structured interviews were also conducted with the teaching team. The questions raised were in the areas of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Participants reported concern in relation to the leaderboard inciting unproductive competition amongst peers. Potential negative outcomes from this could be, based on previous studies, distracting students from their own goals (Corrin & de Barba, 2015) or demotivate students if they see their performance far behind others (Sakulwichitsintu et al, 2015). This finding highlights the tension that designers face whenever displaying performance goal data comparing peers.…”
Section: Discussionmentioning
confidence: 86%
“…Participants reported concern in relation to the leaderboard inciting unproductive competition amongst peers. Potential negative outcomes from this could be, based on previous studies, distracting students from their own goals (Corrin & de Barba, 2015) or demotivate students if they see their performance far behind others (Sakulwichitsintu et al, 2015). This finding highlights the tension that designers face whenever displaying performance goal data comparing peers.…”
Section: Discussionmentioning
confidence: 86%
“…[14] and [15] emphasize on gamification to enhances learning experience and concluded that their design contributed to student-centered learning. In a similar study, [16] identified that students' learning experience improved and as proven by improved academic results as they achieved better scores in practical assignment and overall score. [16] also focused on embedding gamification in the T&L application.…”
Section: Related Workmentioning
confidence: 91%
“…In a similar study, [16] identified that students' learning experience improved and as proven by improved academic results as they achieved better scores in practical assignment and overall score. [16] also focused on embedding gamification in the T&L application.…”
Section: Related Workmentioning
confidence: 91%
“…Existing research shows that learners’ experiences in online environments are influenced by a variety of factors ( Liu and Zhang, 2017 ), and online learning experiences largely influence learners’ intentions and behaviors to continue online learning ( Davis and Wong, 2007 ; Lee, 2010 ). The online learning environment, online learning resources, teacher–student and peer interactions ( Paechter et al, 2010 ), collaborative learning ( Sakulwichitsintu et al, 2015 ), course tasks, and the design of course activities ( Jiang et al, 2019 ) are considered to be important factors influencing online learning experiences. To predict learning behaviors and explore directions and paths for improvement, researchers have applied influence factor modeling to screen and identify influences on learning behaviors ( Alraimi et al, 2015 ).…”
Section: Literature Reviewmentioning
confidence: 99%